Nickel-Catalyzed Selective Synthesis of α-Alkylated Ketones via Dehydrogenative Cross-Coupling of Primary and Secondary Alcohols - Bains, Amreen K; Biswas, Ayanangshu; Adhikari, Debashis (Wiley, 2021)
Herein,we describean isolable,air-stable,homogeneous,nickel catalystthat performsdehydrogenativecross-couplingreactionbetweensecondaryand primaryalcoholsto result α-alkylatedketoneproductsselectively. The sequenceof stepsinvolvein this one-potreactionis dehydrogenationof both alcohols,condensationbetweenthe ketoneand the aldehyde,and hydrogenationof the in situ-generatedα,β-unsaturatedketone.Preliminarymechanisticinvestigationhints a radicalmechanismfollowingborrowinghydrogenreaction
Only IISERM authors are available in the record
Keywords: nickel catalysis; cross-coupling; secon-dary alcohols; radicalreaction